What have we learned from murine models of otitis media? - Tyrer, H; Crompton, M; Bhutta, M (2013)
Otitis media (OM) is a common cause of childhood hearing loss. The large medical costs involved in treating this condition have meant that research to understand the pathology of this disease and identify new therapeutic interventions is important. There is evidence that susceptibility to OM has a significant genetic component, although little is known about the key genetic pathways involved. Mouse models for disease have become an important resource to understand a variety of human pathologies, including OM, due to the ability to easily manipulate their genetic components. This has enabled researchers to create models of acute OM, and has aided in the identification of a number of new genes associated with chronic disease, through the use of mutagenesis programs. The use of mouse models has identified a number of key molecular signalling pathways involved in the development of this condition, with genes identified from models shown to be associated with human OM.